Pengaruh Perputaran Kas, Leverage dan Ukuran Perusahaan Terhadap Profitabilitas pada Perusahaan Manufaktur Subsektor Makanan dan Minuman Yang Terdaftar di BEI (2020-2022) - Elma Oktavianawati; Dwi Ermayanti Susilo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the impact of cash turnover, leverage, and firm size on profitability. The independent variables involved include cash turnover measured by the ratio of net sales to average cash, leverage measured by Debt to Assets Ratio, firm size calculated based on total assets, and profitability measured by Return on Assets as the dependent variable. The research uses financial data from companies in the food and beverage sector listed on the Indonesia Stock Exchange during the period 2020-2022, categorized as secondary data. The research population involves 30 manufacturing companies in the food and beverage sector listed on the IDX. The sampling method used is purposive sampling with 26 companies meeting the selected criteria. Data analysis in the study includes descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing using t-tests. Based on the research findings, it was found that cash turnover has a significant negative and significant impact on profitability, leverage has a significant negative and significant impact on profitability, while firm size does not have a significant impact on profitability.